Effectiveness of mDiabetes intervention in enhancing diabetes awareness and promoting healthy lifestyle changes among the general population in rural India - Rani, Padmaja Kumari; Williams, Jachin David; Jaswal, Nidhi; Yandluri, Venkateswaralu; Sangani, Payal; Sanagavarapu, Kavya; Natarajan, Ramya; Ramalingam, Sandhya; Saligram, Nalini; Khanna, Rohit C. (Frontiers in Public Health, 2025)
AimThis study aimed to assess the impact of a mHealth and community health education intervention on diabetes awareness and promoting healthy dietary and lifestyle habits within a rural population in Andhra Pradesh, India.MethodsUsing a quasi-experimental design, the mDiabetes program was implemented for 1 year, among 1,03,538 rural individuals. Under this program, 56 diabetes prevention messages (twice a week) in local language) were disseminated among the participants via voice calls for a period of 6 months. Additionally, community health education meetings were facilitated by trained community health workers and educational leaflets were distributed among the community members. Questionnaires were administered at three different time points-baseline (before the intervention), endline (after intervention), and follow-up (3 months after endline) to collect demographic data, diabetes-related knowledge, attitudes, practices, physical activity, and dietary habits. Analysis compared data from 545 subjects who participated in all the three surveys.ResultsThe cohort comprised 45.5% males and 54.5% females, aged 19–85 years (mean: 55.42; SD 10.3). Post-intervention, diabetes awareness rose to 97.43% at endline and 99.63% at follow-up from 82.75% at baseline. Belief in diabetes preventability increased from 25.5% to 69.5%, and awareness of lifestyle's impact on diabetes management improved from 72.6% to 80.9%. Over 90% recalled prevention messages, with significant lifestyle changes reported by 83% at endline and 73% at follow-up. Improved dietary and activity habits were evident, with fruit consumption and high-fat food avoidance at 78.5% and 67.7% in follow-up. Physical activity levels improved in both endline and follow-up groups compared to baseline. Daily participation in yoga, running, gym, and aerobics increased to 38.7% in endline and follow-up from 7.3% at baseline (p < 0.001). Outdoor sports engagement rose significantly to 15% in endline and follow-up from 0.5% at baseline (p < 0.001). Regular stair usage (59.8%), walking for chores (84.7%), and short walking breaks (93%) increased significantly in follow-up compared to baseline and endline (p < 0.001).ConclusionThe combined mHealth and community health education intervention improved diabetes awareness and healthy habits in rural areas, showing potential for lasting outcomes and guiding future public health efforts in similar settings.